2012
DOI: 10.1186/1880-6805-31-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex and age-level differences of walking time in preschool children on an obstacle frame

Abstract: BackgroundStepping over an obstacle is a kind of compound movement that makes walking more difficult, especially for preschool children. This study examines sex and age-level differences in walking time in preschool children on an obstacle frame.MethodsThe participants included 324 healthy preschool children: four-year-old boys (51) and girls (51), five-year-old boys (50) and girls (60), and six-year-old boys (62) and girls (50). A 5 cm- or 10 cm-high obstacle (depth 11.5 cm, width 23.5 cm) was set at the half… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 7 publications
1
7
0
1
Order By: Relevance
“…Most of the reliability studies selected in this review were focused on balance (n = 12 [55 %] studies) [19,21,[32][33][34][35][36][37][38][39][40][41]. The tests used to assess balance were many and very heterogeneous, aiming mainly to assess static and dynamic balance.…”
Section: Reliabilitymentioning
confidence: 99%
“…Most of the reliability studies selected in this review were focused on balance (n = 12 [55 %] studies) [19,21,[32][33][34][35][36][37][38][39][40][41]. The tests used to assess balance were many and very heterogeneous, aiming mainly to assess static and dynamic balance.…”
Section: Reliabilitymentioning
confidence: 99%
“…Aoki et al (2011) observed that no sex difference was found in the walking time on a balance beam in 5 and 6 year olds. Also, Kasuga et al (2012a) reported that no sex difference was found in 4-6 year olds in the walking time on the course. Demura et al (1994) examined the sex difference in 3-6 year olds in the walking time on a balance beam and line, and in the times for a series of one-legged hopping and hopping from stone to stone, and reported that a significant sex difference was found only in the time for the series one-legged hopping.…”
Section: Introductionmentioning
confidence: 98%
“…Hence, it is important to adequately evaluate the balance ability. Walking on a balance beam and on a line have often been used to evaluate the dynamic balance of preschool children (Demura, Nagasawa, & Kasuga,1994 ;Aoki, Demura, Kasuga, Shin, & Kawabata, 2011 ;Bürgi, Meyer, Granacher, Schindler, Marques-Vidal, Kriemler, & Puder, 2011;Kasuga, Demura, Aoki, Shin, Sugiura, & Uchida, 2012a;Kasuga, Demura, Aoki, Sato, Shin, & Kawabata, 2012b). However, it is possible that a developmental evaluation of dynamic balance by age may differ according to the type and the degree of difficulty of the tests.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations